3D printed continuous fibre-reinforced composites: Design and characterisation of advanced pseudo-ductile hybrid laminates. (July 2021) - Huang, Cheng; Joosten, Mathew W.
Abstract: A wide-ranging set of hybrid 3D printed continuous fibre UD laminates comprised of polyamide-fibreglass and polyamide-carbon were designed and characterised. The thickness of the carbon layer and the ratio of the carbon and fibreglass layers were varied to investigate the potential for these materials to exhibit a pseudo-ductile response. This is the first study investigating pseudo ductility in 3D printed thermoplastic hybrid composites. The experimental test program showed that with careful design these laminates were capable of exhibiting controlled fragmentation of the carbon layer followed by stable pull out of the fractured material thus exhibiting the desired pseudo-ductile response, thereby, mimicking the behaviour of a ductile metal